Understanding why underrepresented students pursue ecology careers: a preliminary case study. Issue 8 (1st October 2007) - Armstrong, Melissa J.; Berkowitz, Alan R.; Dyer, Lee A.; Taylor, Jason
Abstract : While the literature can tell us something about the number of people from underrepresented populations in science, there is scant evidence to explain why ecology in particular has among the lowest proportions of under‐represented students and professionals of any science. We conducted a case study of 39 African‐American students from ESA's Strategies for Ecology Education, Development, and Sustainability program, focusing on the factors that influenced their choice of an ecology career pathway. Although the case study includes only African‐American students, we review the literature pertaining to all minority groups in science. Our results indicate that family support in particular, along with research experience and a positive view of an ecology career, are important factors in a student's decision to pursue this career path.